Workforce diversity and working environment influences on employee’s morale in PERKESO / Nor Diyana Meor Hedzir and Norasikin Mokhtar - Meor Hedzir, Nor Diyana; Mokhtar, Norasikin (Faculty of Business and Management, 2015)
Employee’s morale is very important in an operation of the organization. The morale of an individual employee can affect how well their performing in their work. Employees that are happy and positive at work are said to have positive or high employee morale. Meanwhile, employees who are dissatisfied and negative about their work environment are said to have negative or low employee morale. The purpose of this study is to determine either workforce diversity or working environment influences employee’s morale in PERKESO. Study shows that from both workforce diversity and working environment, the most influencing toward employee’s morale was workforce diversity which 65% was explain the variance of the employee’s morale.